Pathophysiology & management of Ischemic and Neuropathic pain - Ahmed , Sadaf; Noushad , Shamoon (International Journal of Endorsing Health Science Research, 2014)
Both nociceptive and neuropathic types of pain utilize the same nervous pathway for conduction with considerable physiologic disparities exist in the mechanism through which the body processes and resolves these painful stimuli. Nociceptive pain that results from a known or obvious source (e.g. trauma, cancer metastasis, ischemia, arthritis) is often simple to recognize. Neuropathic pain, however, may occur with the nonappearance of any particular precipitating cause. Anticonvulsants, topical anesthetic agents, antidepressants, antiarrhythmic, anti-inflammatory agents, opioid analgesics, NMDA receptor antagonists, combined analgesic therapy, physiotherapeutic modalities and other ways are used as treatment. Other interventions such as motor cortex stimulation, transcutaneous electrical nerve (TENS) stimulation units, and other peripheral stimulation have been shown to be supportive. A frequent sequella of both types of diabetes is the development of peripheral neuropathy in either motor or sensory nerves, or both. High-frequency TENS can suppress abnormal, spontaneous activity in a damaged peripheral nerve and can block nociceptive transmission in the dorsal horn, the use of this practice seems a practical approach for relief of neuropathic pain. Indeed, TENS applied to the lower extremities of neuropathic pain sufferers reduces the intensity of pain. However what actual molecular mechanism is followed is still a mystery and these studies emphasize for carrying out further work to correlate the neuropathic and ischemic aspects of disorders in these patients.